Contemporary problems and solutions for early childhood music education in Zambia - Emmanuel Tinnash Mulenga; Yan Tu; Dixian Teng (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2021)
Music education is now receiving attention from all works of life especially from psychologist studying children’s mental development scientist has revealed that music education in early childhood helps children develop auditory sense nerves and most of the musical activities aid cycle motor development and children who learn musical instruments have a strong memory function abilities which help them to solve problems in other learning subjects. Learning music in early childhood educations is the bed lock of future education. This is the main reason why early childhood music education researchers are working day and night year in year out to find proper teaching methods to use when interacting with children. As much focus is devoted to studies on children's music education aiding cognitive learning in developing countries, it is a wake-up call for Zambia to develop music education in early childhood education. So this paper investigation endeavors to point out problems and offers sound solutions on the most proficient method to improve music schooling in early childhood education in Zambia by performing a complete overview of the evidence on elementary school education curricula in both government-funded and non-government schools.